Detection of infectious tobamoviruses in irrigation and drainage canals in Greater Poland - Małgorzata Jeżewska; Katarzyna Trzmiel; Aleksandra Zarzyńska-Nowak (Journal of Plant Protection Research, 2018)
Water samples were collected from irrigation ditches and drainage canals surrounding fields in southern Greater Poland. Initially, the samples were subjected to low and highspeed centrifugation and obtained pellets were used to perform biological assays. Viral identification involved biological, electron microscopic as well as molecular methods. The occurrence of Tobacco mosaic virus (TMV) and Tomato mosaic virus (ToMV) was demonstrated in 12 of the 17 examined water sources. The molecular analysis results showed TMV and ToMV co-infections in the analysed water samples. To our knowledge, this is the first report of tobamoviruses being found in environmental water in Poland.